ฤทธิ์คล้ายเอสโตรเจนและฤทธิ์คุมกำเนิดของกวาวเครือขาวที่เก็บไว้เป็นเวลา 25 ปี ในหนูขาว - มะโนเรือง, วสันต์ (Journal of Food Health and Bioenvironmental Science, 2015)
บทคัดย่อ การวิจัยในครั้งนี้มีวัตถุประสงค์เพื่อศึกษาฤทธิ์คล้ายเอสโตรเจนและฤทธิ์คุมกำเนิดของผงป่นแห้งจากหัวกวาวเครือขาว (Pueraria mirifica) ที่เก็บไว้เป็นเวลา 25 ปี ในหนูขาวเพศเมีย โดยได้แบ่งออกเป็น 2 ตอน ได้แก่ ตอนที่ 1 การตรวจสอบฤทธิ์คล้ายเอสโตรเจนของกวาวเครือขาวที่ป้อนให้แก่หนูขาวที่ตัดรังไข่ความเข้มข้น 3 ขนาด (25 50 และ 100 มก./ตัว/วัน) เป็นเวลา 4 วันติดต่อกัน ซึ่งได้แบ่งหนูทดลองออกเป็น 4 กลุ่ม กลุ่มละ 7 ตัว แล้วพิจารณาจากน้ำหนักมดลูกสด แห้ง และของเหลวในมดลูกเปรียบเทียบกับกลุ่มควบคุม และตอนที่ 2 การตรวจสอบฤทธิ์คุมกำเนิดที่ป้อนให้แก่หนูขาวตัวเมีย ขนาด 100 มล./ตัว/วันทุกวัน และปล่อยให้อยู่รวมกับหนูตัวผู้ (ตัวผู้ : ตัวเมีย จำนวน 1 : 2 ตัว/กรง) เป็นเวลา 14 วัน แล้วแยกตัวเมียเลี้ยงต่อไปอีก 21 วัน สังเกตการตั้งท้องระหว่างการเลี้ยง พร้อมทั้งบันทึกจำนวนลูกหนูที่เกิด หากหนูไม่คลอดในระหว่างการเลี้ยง จะทำการผ่าตัดเพื่อตรวจการฝังตัวของตัวอ่อนในมดลูก พิจารณาผลการตั้งท้องและจำนวนลูกที่เกิด เปรียบเทียบกับกลุ่มควบคุม ผลการวิจัยพบว่ากวาวเครือขาวที่เก็บไว้เป็นเวลา 25 ปีนั้น ยังคงมีฤทธิ์คล้ายเอสโตรเจนอยู่ คิดเป็นร้อยละ 100 โดยพบว่าน้ำหนักของมดลูกสด แห้ง และปริมาณของเหลวในมดลูกหนูขาวที่ตัดรังไข่ของกลุ่มที่ได้รับกวาวเครือขาวมีค่ามากกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.01 ส่วนฤทธิ์คุมกำเนิดพบว่า กวาวเครือขาวที่เก็บไว้เป็นเวลา 25 ปียังคงสามารถแสดงฤทธิ์คุมกำเนิดหนูขาวได้ โดยพบว่าหนูขาวกลุ่มที่ได้รับกวาวเครือขาวนั้นยังคงมีการตั้งท้องอยู่ คิดเป็นร้อยละ 20 คำสำคัญ: กวาวเครือขาว ฤทธิ์คล้ายเอสโตรเจนและฤทธิ์คุมกำเนิด หนูขาว Abstract The objective of this study was to investigate the estrogenic and antifertility effects of Pueraria mirifica tuber powder which was collected for 25 years since 1987 in female rats. There were 2 experiments in this study. The first experiment was the investigation of P. mirifica estrogenic effects in ovariectomized mature rats by oral feeding with 3 different dosages of P. mirifica (25, 50 and 100 mg./rat/day) for 4 consecutive days comparing with control group (7 rats/group). Uterine wet and dried weight and liquid content were used as the indicators of the P. mirifica estrogenic potency. The second experiment was investigation on the antifertility effects of P. mirifica in mature female rats. Two female rats were caged with 1 male in each cage (10 cages/group). The highest dosage of P. mirifica in the first experiment was feed to only the female rats for 14 consecutive days comparing with the control group. After 14-day treatment of P. mirifica to the females, the male rats from both groups were seperated and the female rats were left and stayed in each cage for another 21 days. During 21-day of observation, the number of pregnant and parturient rats and the number of live fetuses delivered were noted. In the 22th day, all of the female rats in each group were sacrificed and noted for the number of embryos IN UTERO of pregnant rats. The results were found that P. mirifica collected for 25 years still pronounced the estrogenic activities (100 %) in bilaterally ovariectomized rats as indicated from the uterine wet and dried weight and liquid content were significantly higher than the control group (p<0.01). The studies on the antifertility effects of 25th yr. P. mirifica in mature female rats revealed that 25th yr. P. mirifica was still effective in control female rats fertility. There were 20 % pregnant rats in the experimental group. Keyword: Pueraria mirifica, estrogenic and antifertility effects, rat